2020
DOI: 10.1038/s41467-020-15913-6
|View full text |Cite
|
Sign up to set email alerts
|

Integrative multiplatform molecular profiling of benign prostatic hyperplasia identifies distinct subtypes

Abstract: Benign prostatic hyperplasia (BPH), a nonmalignant enlargement of the prostate, is among the most common diseases affecting aging men, but the underlying molecular features remain poorly understood, and therapeutic options are limited. Here we employ a comprehensive molecular investigation of BPH, including genomic, transcriptomic and epigenetic profiling. We find no evidence of neoplastic features in BPH: no evidence of driver genomic alterations, including low coding mutation rates, mutational signatures con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 68 publications
(86 reference statements)
1
46
1
Order By: Relevance
“…Since BPH patients have one or more of a variety of histological features, including stromal nodules, glandular nodules, and/or fibrosis, this disease is more likely a combination of conditions ( 51 ). Recent molecular profiling studies have provided a basis for at least two BPH subtypes ( 12 ). As in prostate development, it has long been clear that paracrine interactions between stromal and epithelial tissues are important in BPH ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since BPH patients have one or more of a variety of histological features, including stromal nodules, glandular nodules, and/or fibrosis, this disease is more likely a combination of conditions ( 51 ). Recent molecular profiling studies have provided a basis for at least two BPH subtypes ( 12 ). As in prostate development, it has long been clear that paracrine interactions between stromal and epithelial tissues are important in BPH ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…The only definitive risk factors for developing BPH are male sex and increasing age, but BPH has been linked to decreased systemic androgen:estrogen ratios, obesity, type 2 diabetes, metabolic syndrome, and inflammation ( 39 ). There is a paucity of studies investigating possible genetic determinants of BPH, although, more recently, there has been greater interest in this area ( 1012 ). The medical therapeutic options used for men with LUTS related to BPH are limited (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…While BPH-A subtype is characterised by stromal-tissue-like features, BPH-B subtype has specific dysregulations involving metabolic pathways in the patients with obesity (BMI>30) and hypertension. Abnormal metabolism is also reported in BPH-A subgroup when compared to age-matched control samples (Liu et al, 2020;Tomlins et al, 2007). BPH-A subtype has been correlated with mTOR inhibition in 50% of the nominated sample of BPH-A subgroup and has been investigated as a potential therapeutic option for BPH patients (Fingar et al, 2002;Tumaneng et al, 2012).…”
Section: Pathophysiologymentioning
confidence: 98%
“…According to the recently published molecular profiling, two biologically distinct BPH subtypes have been identified, which were referred to as BPH-A subgroup and BPH-B subgroup (Liu et al, 2020). While BPH-A subtype is characterised by stromal-tissue-like features, BPH-B subtype has specific dysregulations involving metabolic pathways in the patients with obesity (BMI>30) and hypertension.…”
Section: Pathophysiologymentioning
confidence: 99%
“…In fact, in a recent NGS study, no evidence of driver genomic alterations was found in BPH cases, inconsistent with a neoplastic process. Even they observed multiple signatures related to the inactivation of KRAS signaling [117].…”
Section: ãããmentioning
confidence: 99%